Consumers' acceptance of smart virtual closets. (November 2016) - Perry, Anna
Abstract: The purpose of the study is to investigate how various factors influence consumers' adoption intention of smart virtual closets. An extended technology acceptance model was proposed with three additional factors: a social influence variable (subjective norm), a personality trait (technology optimism), and a product feature (aesthetics). The results confirmed all relationships in the original technology acceptance model (e.g., usefulness→attitude, ease of use→attitude, usefulness→intention, and attitude→intention) and indicated significant relationships of all new proposed paths. All three factors, subjective norm, technology optimism, and aesthetics, significantly affected consumers' perceptions of ease of use and usefulness. However, instead of a positive relationship, subjective norm negatively influenced perceived ease of use. In addition, subjective norm also directly influenced usage intention. These findings advance theory and provide a solid basis for businesses aimed at improving user adoption of smart virtual closets.